Modelling nonlinear economic time series - Teräsvirta, Timo 1941-; Granger, C. W. J. 1934-2009; Tjostheim, Dag (Oxford University Press, 2010)
A comprehensive assessment of many recent developments in the modelling of time series, this text introduces various nonlinear models and discusses their practical use, encouraging the reader to apply nonlinear models to their practical modelling problems
Includes bibliographical references and index
Keywords: Multivariate Analyse; Zeitreihenanalyse; Econometric models; Time-series analysis; Nonlinear theories